The Cambridge prehistory of the Bronze and Iron Age Mediterranean - Knapp, Arthur Bernard; Knapp, Arthur Bernard (Cambridge Univ. Press, 2014)
The Cambridge Prehistory of the Bronze and Iron Age Mediterranean offers new insights into the material and social practices of many different Mediterranean peoples during the Bronze and Iron Ages, presenting in particular those features that both connect and distinguish them. Contributors discuss in depth a range of topics that motivate and structure Mediterranean archaeology today, including insularity and connectivity; mobility, migration, and colonization; hybridization and cultural encounters; materiality, memory, and identity; community and household; life and death; and ritual and ideology. The volume's broad coverage of different approaches and contemporary archaeological practices will help practitioners of Mediterranean archaeology to move the subject forward in new and dynamic ways. Together, the essays in this volume shed new light on the people, ideas, and materials that make up the world of Mediterranean archaeology today, beyond the borders that separate Europe, Africa, and the Middle East